014 Ictal consciousness in epilepsy vs non-epileptic attack disorder. Issue 10 (24th September 2010) - Ali, F; Bagary, M; Greenhill, L; McCorry, D; Rickards, H; Cavanna, A E
Abstract : Aims: Varying linguistic profiles between patients with epilepsy and patients with non-epileptic attack disorder (NEAD) may reflect underlying variations in subjective seizure experience (Plug et al 2009). We hypothesised that exploration of subjective seizure symptoms could enhance knowledge of the differing natures between epilepsy and NEAD. We performed a quantitative evaluation of both the contents of consciousness and the general level of awareness during seizures using the Ictal Consciousness Inventory (ICI) (Cavanna et al 2008). Methods: Ninety-one adult out-patients attending general neuropsychiatry/epilepsy clinics (Department of Neuropsychiatry, BSMHFT and University of Birmingham) with established diagnoses of either epilepsy (n=62) or NEAD (n=29) completed an ICI for each witnessed seizure. A total of 155 questionnaires (epilepsy: n=111; NEAD=44) were generated. ICI-Level (ICI-L) and ICI-Content (ICI-L) scores were calculated. Results: Mann-Whitney U Test demonstrated statistically significant higher ICI-L and ICI-C scores in NEAD (p=0.01). Conclusions: Subjective reports of consciousness experiences vary between NEAD/epilepsy. Patients with NEAD report significantly greater levels of general awareness/responsiveness and higher degrees of subjective content during attacks. Larger cohorts are required to confirm evidence for the potential usefulness of the ICI in enhancing understanding of subjective seizure experiences and supporting differential diagnosis. References—Cavanna AE, Mula M, Servo S, Strigaro G, Tota G, Barbagli D, Collimedaglia L, Viana M, Cantello R, Monaco F. Measuring the level and contents of consciousness during epileptic seizures: the Ictal Consciousness Inventory. Epilepsy and Behaviour 2008;13:184–188. Plug L, Sharrack B, Reuber M. Seizure metaphors differ in patients' account of epileptic and psychogenic nonepileptic seizures. Epilepsia